2016
DOI: 10.1002/aenm.201501927
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stress Factors on the Adhesion of Interfaces in R2R Fabricated Organic Photovoltaics

Abstract: The role of the common stress factors such as high temperature, humidity, and UV irradiation on interface adhesion of roll‐to‐roll fabricated organic photovoltaic (OPV) devices is investigated. The samples range from bare front electrodes to complete devices. It is shown that applying single stress or combinations of stresses onto the samples variably affect the adhesion properties of the different interfaces in the OPV device. It is revealed that while the exposure of the complete devices to the stresses resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Notably, the cohesive fracture energy of the highest-performing/optimal all-PSCs (2.45 ± 0.3 J m –2 ) was 9-fold higher than that of the optimal PCBM–PSCs (0.29 J m –2 ), which highlights the strong fracture resistance of all-PSCs. Over the past few years, different methods, such as annealing, UV radiation, and moisture treatment, have been employed to further improve the low fracture energy of PCBM–PSCs. , However, these methods often lower the PCE of solar cells and significantly accelerate the degradation of the device performance. Therefore, our results suggest that the fracture energy of PSCs can be increased substantially without additional treatments by using a polymeric, rather than a small-molecule (i.e., PCBM), electron acceptor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Notably, the cohesive fracture energy of the highest-performing/optimal all-PSCs (2.45 ± 0.3 J m –2 ) was 9-fold higher than that of the optimal PCBM–PSCs (0.29 J m –2 ), which highlights the strong fracture resistance of all-PSCs. Over the past few years, different methods, such as annealing, UV radiation, and moisture treatment, have been employed to further improve the low fracture energy of PCBM–PSCs. , However, these methods often lower the PCE of solar cells and significantly accelerate the degradation of the device performance. Therefore, our results suggest that the fracture energy of PSCs can be increased substantially without additional treatments by using a polymeric, rather than a small-molecule (i.e., PCBM), electron acceptor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…37,39,40 We probed the uorescence decay dynamics of PF12TBT lm and its blend lms, including PF12TBT/PTB7-Th and PF12TBT/P(NDI2OD-T2) blend lms. The uorescence decay was tted with a two component-exponential function (the specic data are shown in Table S1 †), then the mean lifetime was calculated by weighting the amplitude of each component employing eqn (1). The energy transfer efficiency (ETE) is given by eqn (2):…”
Section: Resultsmentioning
confidence: 99%
“…Polymer solar cells (PSCs) have attracted great attention in the past decade as a renewable energy due to their potential for lowcost fabrication and roll-to-roll production of exible plastic solar modules. [1][2][3][4][5][6] Since the original work of Tang, 7 the power conversion efficiency (PCE) of PSCs based on bulk heterojunction (BHJ) materials comprising p-conjugated polymers as electron donating materials and fullerene derivatives as electron-accepting materials has increased dramatically up to 10% with the development of low-bandgap materials and advance in device architectures. [8][9][10][11] However, fullerene derivatives suffer from disadvantages, such as relatively weak absorption ability in the visible region, energetic tenability and thermally unstable morphology, which limits the design of complementary polymer donors for maximum performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other stability studies of large area OPV cells and modules have been performed testing different experimental variables such as: i) Single-junction versus tandem devices; [394] ii) different encapsulation protocols (complete; partial); [170] iii) different encapsulation barrier foils; [209] iv) different adhesives (UV-curable; pressure-sensitive); [207] v) the effect of edge sealing; [374,383] vi) the lifetime reproducibility among different laboratories; [371] and vii) combined application of different stress factors on the adhesion of OPV interfaces in large area R2R devices. [395] However, in all of these studies the reported values of T 80 were <<1 year.…”
Section: Stability Of Large Area Cells and Modulesmentioning
confidence: 88%